The Effect of Climate Change on Humans and Animals - Sunanda. I. Kittali (AG Volumes, 2022)
We must remember that climate change’s impacts on biodiversity are linked with its own impacts. Human activity contributes to the accumulation of greenhouse gases and disrupts the natural balance of atmospheric greenhouse gases, which in turn contributes to the loss of biodiversity. Coastal habitats might be flooded, and the ocean’s nitrogen supply to land ecosystems could be halted if sea levels rise. Wildlife’s behavior, growth, foraging, migration, and reproduction are directly impacted by climate change. Environmental factors such as ecosystem productivity, hydrological balance, biomass production, and interactions among trophic levels might be harmed if global warming continues. Natural disasters are becoming more intense, and the patterns of natural disturbance are shifting as a result of climate change. Such processes put terrestrial ecosystems under physiological and environmental stress, which has a negative impact on their resistance and resilience. In addition, the warming atmosphere shifts the thermal optimum to higher latitudes and higher altitudes, resulting in more extreme temperatures. Plants and animals in the terrestrial biota adapt quickly to temperature changes by shifting their geographic ranges toward more hospitable climatic circumstances. Photoperiod, for example, is a climatic element that drives life history events, but the time of spring weather is altering as a result of greenhouse gasses. Phenomenological elements like as mating and breeding, hibernation, and post-hibernation activity might be mismatched, resulting in certain species being handicapped while others benefit. As a consequence, new ecologies will emerge. As the temperature rises, parasites and disease-causing agents in animals are able to reproduce and thrive at a much higher rate, as well as transmit their diseases. Changes in the climate disrupt the interrelationships between species, as well as a wide range of ecological services. When it comes down to it, global warming threatens native terrestrial fauna and changes ecological processes.